2012
DOI: 10.4172/2155-6156.1000180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin Administration on the Pregnancy Outcome of Diabetic Rats

Abstract: Objective: Investigate the effects of diabetes and treatment with quercetin on the maternal reproductive performance and impact on foetal growth. Study design:A total of 32 female Wistar rats were distributed into four groups: non-diabetic (G1); non-diabetic treated with quercetin (G2); diabetic (G3) and diabetic treated with quercetin (G4). At day 21 of pregnancy, each rat was anesthetized and humanely killed for laparotomy; was observed reproductive performance, foetal and placental weights and the placental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Another study indicated that quercetin might have an antioxidant effect and prevented the renal tubular damage and decreased oxidative stress arising from induced by chronic cadmium administration (41). The treatment with quercetin in diabetic rats causes an increased number of corpora lutea and maternal weight gain (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicated that quercetin might have an antioxidant effect and prevented the renal tubular damage and decreased oxidative stress arising from induced by chronic cadmium administration (41). The treatment with quercetin in diabetic rats causes an increased number of corpora lutea and maternal weight gain (23).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment with quercetin in diabetic rats causes an increased number of corpora lutea and maternal weight gain (23). Quercetin is a potential drug with antidiabetic and anti-hyperglycemic functions mediated by changes in the levels of glucose, cholesterol, and triglycerides (41). The findings propose that quercetin therapy has protective efficacy in diabetes by regressive oxidative stress and the maintenance of pancreatic-cell integrity (42).…”
Section: Discussionmentioning
confidence: 99%
“…[99][100][101][102] Although the underlying chemopreventive and chemotherapeutic mechanisms are needed to be elucidated, flavonoids have been thoroughly investigated as to how they modulate various key elements in cellular signal transduction pathways and their effect on cell fate determination processes. [103][104][105] Most dietary flavonoids not only inhibit the growth of tumor cells but also promote cell differentiation by quenching oxidative stress and inflammatory response.…”
Section: Utilisation Of Nanomedicine In Varied Applications Of Flavonoidsmentioning
confidence: 99%
“…In another study [106] it was observed that quercetin may inhibit proinflammatory cytokines production in pregnant mice, especially IL-6 and IL-8. Additionally, Braga et al [107] investigated the effects of quercetin on the maternal reproductive capacity and fetal and placental development in diabetic rats. They showed that quercetin did not improve reproductive capacity, neither fetal nor placental development; however quercetin controlled glucose levels and promoted weight gain compared to untreated diabetic rats.…”
Section: Quercetin Intake During Pregnancymentioning
confidence: 99%
“…Results of meta-analysis of clinical trials [43] have shown that the impact of quercetin on blood pressure was reported in a total of 7 trials (587 patients) with results revealing significant reductions in both systolic and diastolic blood pressure following quercetin supplementation at doses from 100 mg/day to 1000 mg/day from 4 to 10 weeks [93, 107, 133–137]. In summary, the randomized controlled trials show that a significant reduction in systolic and diastolic blood pressure may be expected with quercetin doses ≥500 mg/day and the effect is insignificant with doses <500 mg/day [43].…”
Section: Clinical Trials and Meta-analysismentioning
confidence: 99%